PENGARUH KEPEMIMPINAN DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PT. HITACHI CHEMICAL INDONESIA - Rahmadhani, Dita; Ratnasari, Ina (Journal for Management Student (JFMS), 2021)
This study further examines the influence of the influence of leadership and work motivation on employee performance at PT. Hitachi Chemical Indonesia. The research was conducted using descriptive quantitative and verification methods, namely collecting, presenting, analyzing, and testing hypotheses, as well as making conclusions and suggestions. Samples were collected using stratified random sampling method with a total sample of 108 respondents from a population of 147 employees. The data analysis techniques used were scale range analysis and path analysis, Microsoft Excel computer program, and SPSS version 16. From the results of research data analysis, several conclusions were obtained as follows: Leadership at PT. Hitachi Chemical Indonesia is in good criteria, motivation is in good criteria, employee performance is in good criteria. From the results of the analysis there is a correlation between leadership and motivation with a value of 0.565, meaning that it has a moderate and two-way correlation because it is positive. There is a partial influence of leadership of 21.5% on the performance of employees of PT. Hitachi Chemical Indonesia and motivation have an effect of 69.3%. Thus there is a simultaneous influence of leadership and motivation on employee performance.